"But All Had Great Reason to Dread!": Religion, Affect, and Conspiracy in the Stamp Act Crisis. Issue 2 (June 2022) - Urich, Joshua D.
Abstract: This article explores affective and emotional components of conspiracism in the 1765 Boston Stamp Act Crisis. Once a common subject in the study of Revolutionary America, conspiracism has disappeared from the historiography in recent decades. I argue that this is a serious oversight in understanding religion in the Revolutionary era. Unmasking conspiratorial plots against colonial liberties was a religious experience in the colonies, simultaneously imbuing liberty with a felt sense of sacredness and forging an emotional separation between the colonies and England. In making this claim, this article aims to demonstrate how scholars of religion might incorporate affect into the historical study of religion. Attention to affective cues, particularly in religious texts, sheds light on the phenomenology of historical religion. Through such analysis, we can begin to understand how religious communities formed through affective connections to the sacred, what that sacred felt like, and how bodily and emotional experience shaped reactions to violations of the sacred. In the case of the Stamp Act Crisis, conspiracism, anti-Catholicism, and satanic symbolism sparked an affectively charged moment characterized by fear, disgust, and anger. As colonists participated in unmasking supposed Catholic and Parliamentary conspiracies against them, they created a community united around scared liberty.